Altitudinal Shifts as a Climate Resilience Strategy for Angelica sinensis Production in Its Primary Cultivation Region - Zhengdong Li; Dajing Li; Hongxia Peng; Ruixuan Xu; Zaichun Zhu (Remote Sensing, 2025)
Angelica sinensis, a highly valued Chinese herb renowned for its medicinal and nutritional properties, occupies a distinctive position in montane agriculture. The remote sensing monitoring of grain crops and their driving factors has been extensively studied, yet research on medicinal cash crops, particularly Angelica sinensis, remains limited. This study employed Landsat imagery and a two-step supervised classification method to map Angelica sinensis cultivation areas in southern Gansu Province while also assessing and projecting climate change impacts on its spatial distribution and yield based on the MaxEnt model and CMIP6 models. The results revealed a pronounced upward altitudinal shift in Angelica sinensis cultivation between 1990 and 2020, with the proportion of cultivation areas above 2400 m increasing from 28.75% to 67.80%. Climate factors explained 59.07% of the spatial distribution of Angelica sinensis, with precipitation, temperature, and altitude identified as the key environmental factors influencing its spatial distribution, yield, and growth. Projections for 2020 to 2060 indicate that Angelica sinensis cultivation areas will continue to shift to higher altitudes, accompanied by overall declines in both suitable area and yield. Under the SSP5-8.5 scenario, nearly all suitable areas are expected to be confined to altitudes above 2400 m by 2060, with 41.46% occurring above 2800 m. By 2060, the yield is expected to decrease to 361–421 kg/mu (down 20–31% from 2020) while the suitable area is projected to shrink to 0.98–1.80 million mu (40–60% smaller than 2040) under different scenarios. This study provides new insights into the protection and sustainable management of Angelica sinensis under changing climatic conditions, offering a scientific basis for the sustainable utilization of this valuable medicinal plant.